Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/2016jc011679
|View full text |Cite
|
Sign up to set email alerts
|

A validated tropical-extratropical flood hazard assessment for New York Harbor

Abstract: Recent studies of flood risk at New York Harbor (NYH) have shown disparate results for the 100 year storm tide, providing an uncertain foundation for the flood mitigation response after Hurricane Sandy. Here we present a flood hazard assessment that improves confidence in our understanding of the region's present‐day potential for flooding, by separately including the contribution of tropical cyclones (TCs) and extratropical cyclones (ETCs), and validating our modeling study at multiple stages against historic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 51 publications
3
103
0
Order By: Relevance
“…ETC winds can on occasion reach hurricane force and cause damaging coastal storm surges. Orton et al () found that in the New York City area, ETCs are a dominant cause of surge events that have an annual probability greater than 1%. The National Oceanic and Atmospheric Administration (NOAA) National Climatic Data Center (NCDC) estimated that from 1980 to 2016, major ETC events caused more than $1 billion in damage for each event (https://www.ncdc.noaa.gov/billions/summary-stats).…”
Section: Atmospheric Circulation and Transportmentioning
confidence: 99%
“…ETC winds can on occasion reach hurricane force and cause damaging coastal storm surges. Orton et al () found that in the New York City area, ETCs are a dominant cause of surge events that have an annual probability greater than 1%. The National Oceanic and Atmospheric Administration (NOAA) National Climatic Data Center (NCDC) estimated that from 1980 to 2016, major ETC events caused more than $1 billion in damage for each event (https://www.ncdc.noaa.gov/billions/summary-stats).…”
Section: Atmospheric Circulation and Transportmentioning
confidence: 99%
“…To date, most of the historical storm surge and wave modeling studies for the U.S. East and Gulf Coasts have focused on individual TCs in a specific region (e.g., Bilskie et al, ; Bunya et al, ; Dietrich et al, ; Hope et al, ; Kennedy et al, ; Lin et al, ; Marsooli et al, ; Orton et al, ; Shen et al, ; Sheng et al, ; Westerink et al, ). In addition to historical surge and wave modeling, probabilistic flood hazard assessment studies also usually focus on a specific region (e.g., Lin & Emanuel ; Lin et al, ; Orton et al, ). Despite the appreciable number of storm‐specific and region‐specific studies, storm surge and wave conditions over the entire basin (of the U.S. Atlantic Coast) are rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…ETC winds sometimes reach hurricane force and drive 35 damaging coastal storm surge. Orton et al (2016) found that in the New York City 36 area, ETCs are the dominant cause of surge events that have annual probability 37 greater than 1%. NOAA's NCDC estimated $40.9 billion in insured and uninsured 38 losses due to ETC events from 1980 to 2016 that caused more than one billion 39 dollars in damage each (www.ncdc.noaa.gov/billions/summary-stats; see also Smith 40 and Katz, 2013).…”
Section: Introduction 29 30mentioning
confidence: 99%